Technology and events how to create engaging events - Martin, Vanessa (Goodfellow Publishers Limited, 2016)
Explores the use of technology to improve results on all kinds of events from initial planning stages right through to post event debriefing. This book provides all the solutions and tips on how to maximize the participation of your audience, cut costs and have better revenues from your events."